Analisis Genus dan Penyakit Karang di Perairan Pulau Tuan Kecamatan Peukan Bada Kabupaten Aceh Besar - Nadia Aldyza; Afkar , (Universitas Islam Negeri Ar-Raniry, 2015)
This study aims to determine the genus of coral and coral diseases in the coral reef ecosystem of Tuan Island Peukan Bada, Aceh Besar District. The data of coral genera were gathered by using point intercept transect method, whereas, the data of coral diseases were gathered by using survey method. The data were identified by using handbook and then analyzed descriptively. The results showed that there were 5 coral genera found in Tuan Island Pekan Bada namely: Acropora, Montipora, Pocillopora, Porites, and Goniastrea. Meanwhile, coral diseases that are found in Tuan Island were ulcerative white spots, growth anomalies of an unknown cause, sediment damage, alga overgrowth, pink line disease dan pigmentation responses. The conclusion of this study were (1) the coral reefs that were found in Tuan Island Peukan Bada, Aceh Besar District consisted of 5 genera, and (2) coral diseases in Tuan Island consisted of 6 types of diseases.